2020
DOI: 10.1002/ett.4001
|View full text |Cite
|
Sign up to set email alerts
|

Joint subchannel assignment and power control in OFDMA in‐band full‐duplex heterogeneous networks

Abstract: Among the emerging technologies for the fifth‐generation (5G) cellular networks, in‐band full‐duplex (FD) wireless communication and heterogeneous networks (HetNets) are two promising technologies, which can significantly improve the network capacity. Due to self‐interference (SI) and multiple sources of intercell interference, base station (BS)‐BS interference and user equipment (UE)‐UE interference in FD HetNets, interference management is a significant and challenging issue in such a network. To this end, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Additionally, numerous resource allocation methods based on frequency reuse techniques have been developed for 5G communication in cellular networks. [30][31][32][33][34][35] In the proposed technique, 30 macro users located in the intermediary region (the border of the center region) are served more resources due to good channel conditions close to the serving base station, while femto users are assigned resource blocks from sub-bands. In terms of throughput and outage performance, numerical findings claim that the proposed system has better results than the previous techniques.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, numerous resource allocation methods based on frequency reuse techniques have been developed for 5G communication in cellular networks. [30][31][32][33][34][35] In the proposed technique, 30 macro users located in the intermediary region (the border of the center region) are served more resources due to good channel conditions close to the serving base station, while femto users are assigned resource blocks from sub-bands. In terms of throughput and outage performance, numerical findings claim that the proposed system has better results than the previous techniques.…”
Section: Related Workmentioning
confidence: 99%
“…QoS aspects in FD networks were considered by other works 22‐28 . da Silva et al 22 studied the joint problem of RB assignment, UE pairing, and power allocation as a mixed integer nonlinear problem that was solved by a novel joint fairness assignment maximization algorithm.…”
Section: State‐of‐the‐art and The Main Contributionsmentioning
confidence: 99%
“…Although a heuristic solution was proposed therein, no optimal solution was provided and mode selection was not discussed. The same problem was studied by Rajabi et al 27 in a heterogeneous network, where they invoked variable change and linear approximation to convert the original problem into a tractable mixed‐integer linear programming. Finally, Yu et al 28 formulated a joint UE scheduling, and channel allocation problem to maximize the total data rate with individual data rate requirements.…”
Section: State‐of‐the‐art and The Main Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These applications need a higher quality of service (QoS) and more communication resources than traditional applications 1 . Over the past few years, with the increasing popularity of smart‐phones and devices with powerful multimedia capabilities, the amount of data traffic has been doubled every year 2 . Recent research has indicated that more than 80% of mobile traffic is originated at home or work, but about half of these premises suffer from poor indoor coverage 3 .…”
Section: Introductionmentioning
confidence: 99%